Sense of happiness and other aspects of quality of life in patients with obsessive-compulsive disorder - Żerdziński, Maciej; Burdzik, Marcin; Żmuda, Roksana; Witkowska-Berek, Agnieszka; Dȩbski, Paweł; Flajszok-Macierzyńska, Natalia; Piegza, Magdalena; John-Ziaja, Hanna; Gorczyca, Piotr (Frontiers in Psychiatry, 2022)
Quality of life (QoL) is the intellectual and emotional well-being of an individual, which is determined by many factors. The most measurable are the sense of happiness, occupational satisfaction, quality of interpersonal relationships and sex life. Obsessive-compulsive disorder (OCD) is a chronic mental disorder diagnosed by the presence of obsessions and compulsions that disrupt normal psychosocial functioning. Despite early onset, treatment is delayed (OCD-DTI) and unsatisfactory. The primary objective of this study is to assess selected correlates of the sense of happiness among patients with OCD. The secondary objective is to compare the sense of happiness with healthy people. Seventy-five OCD patients and equal number of healthy subjects were compared using a Polish adaptation of the Oxford Happiness Questionnaire (OHQ-23). We found a significant negative correlation between sense of happiness and the severity of OCD (r= -0.479), the number of obsessive-compulsive personality traits (r=-0.323), the number of other comorbid mental disorders (r=-0.272), the level of aggression (r=-0.448), impulsivity (r=-0.301), depressiveness (r=-0.357) and the sexual dysfunctions (r=-0.279). The latter were much more common in individuals with OCD compared to healthy subjects (66.67% vs 12%). The level of loneliness was over two times higher in the study group compared to controls (27% vs 12%). The mean delay in treatment onset was 13 years. Assessment of aspects of QoL should be an integral part of the diagnostic and therapeutic process in OCD.